PERAN KEPEMIMPINAN DALAM PENERAPAN TIGA ASPEK MANAJEMEN SATU MENIT (PUJIAN, TEGURAN DAN PERMINTAAN MAAF) DI MI DARUSSALAM SAMARINDA - Nur Malik, Novi; Eka Wardhana, Kautsar (Journal of Sustainable Transformation, 2024)
This research aims to examine the effectiveness of leadership in implementing the three main aspects of 1-minute management, namely praise, reprimand and apology at Madrasah Ibtidaiyah Darussalam. In educational leadership, madrasa heads play a strategic role in motivating and developing teaching and educational staff performance. This research used a qualitative descriptive method with a literature study approach and data collection through an online questionnaire distributed to 15 respondents consisting of teachers and madrasa staff. Data analysis was carried out using theme analysis techniques to identify patterns of behavior and responses to the three aspects of leadership. The results showed that the praise by madrasah heads significantly increased teacher motivation and self-confidence, while reprimands given constructively helped improve performance. In addition, a leader's attitude of apologizing when they make a mistake creates a more inclusive work environment and increases subordinates' trust in leadership. These findings indicate that leadership that integrates praise, reprimand, and apology can build positive relationships and improve performance in the educational environment.